2022
DOI: 10.12688/f1000research.26598.2
|View full text |Cite
|
Sign up to set email alerts
|

Creating and sustaining collaborative multi-institutional industry site visit programs: a toolkit

Abstract: Background: As more early career scientists enter into diverse career pathways, visiting local companies or organizations can support their exploration of these paths. As an efficient way to facilitate this, we developed a collaborative regional site visit program: the Enhancing Local Industry Transitions through Exploration (ELITE) Consortium.  Consortium members arrange half-day visits to local industry sites, thus providing companies and trainees the opportunity to meet and identify potential professional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…These concerns were debunked by a robust cross‐institutional analysis from 10 NIH BEST institutions, who pooled their data on student participation in career development activities to demonstrate conclusively that engaging in such activities did not extend time‐to‐degree in graduate school or decrease the number of first‐author or total publications of graduate students 25 . Furthermore, the NIH BEST experiment demonstrated that there are a variety of ways for PhD students and postdocs to engage in meaningful experiential career learning opportunities in non‐academic laboratory work environments, many of which do not require extended time away from the laboratory 37–43 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These concerns were debunked by a robust cross‐institutional analysis from 10 NIH BEST institutions, who pooled their data on student participation in career development activities to demonstrate conclusively that engaging in such activities did not extend time‐to‐degree in graduate school or decrease the number of first‐author or total publications of graduate students 25 . Furthermore, the NIH BEST experiment demonstrated that there are a variety of ways for PhD students and postdocs to engage in meaningful experiential career learning opportunities in non‐academic laboratory work environments, many of which do not require extended time away from the laboratory 37–43 …”
Section: Discussionmentioning
confidence: 99%
“… 25 Furthermore, the NIH BEST experiment demonstrated that there are a variety of ways for PhD students and postdocs to engage in meaningful experiential career learning opportunities in non‐academic laboratory work environments, many of which do not require extended time away from the laboratory. 37 , 38 , 39 , 40 , 41 , 42 , 43 …”
Section: Discussionmentioning
confidence: 99%
“…Targeted career-development programming and professional-development training can assist in career placement [ 32 ] without hindering productivity or efficiency [ 12 ]. In addition to NIGMS funding requirements for career outcomes reporting, recent efforts to increase career outcomes reporting have enabled more rigorous evaluation of such outcomes [ 4 , 10 , 33 36 ].…”
Section: Discussionmentioning
confidence: 99%